MEMBANGUN SIKAP SOSIAL YANG POSITIF MELALUI PROGRAM PENDIDIKAN LINGKUNGAN DI SEKOLAH DASAR - Yuyun, Wa; Herlina, Herlina; Gue, Angela; Inon, La Ode (Jurnal Sultra Elementary School, 2023)
Environmental education in elementary schools not only aims to raise awareness of environmental issues, but can also play an important role in building positive social attitudes among students. Environmental education programs implemented in elementary schools can introduce social values such as cooperation, empathy, responsibility, and respect for others. Through environmental-based activities, students can develop attitudes that care about social and environmental issues, and play an active role in creating positive changes in their communities. This study aims to examine the role of environmental education in building positive social attitudes in elementary school students through an in-depth literature study. The results of the study indicate that an integrated environmental education program can increase social awareness and shape students' characters who are more concerned about others.